PELATIHAN PEMBUATAN PUPUK ORGANIK DENGAN DEKOMPOSER MICROBACTER ALFAAFA-11 (MA-11) di DESA GAPUK KECAMATAN SURALAGA - Muhammad Joni Iskandar; Dwi Haryati Ningsih; Rini Endang Prasetyowati; Rizal Ahmadi (Fakultas Pertanian, Universitas Gunung Rinjani, 2022)
The need for organic fertilizers is always increasing in the development of food crops in Indonesia, especially in the East Lombok Regency. The increase in fertilizer demand was driven by the scarcity of fertilizers and the lack of subsidized fertilizers in various regions. In processing livestock manure such as cow manure, it is still very minimal because farmers in the area have not processed it optimally. This is because cow dung is considered to cause an unpleasant odor, is dirty and can cause many diseases, causing the desire to throw it away. Whereas cow dung can be utilized optimally as the main ingredient for making compost. Efforts to add compost activator can be done by adding MA-11 or better known as microbacter alfaafa-11 as the main decomposer. The purpose of this community service (PKM) is for farmer groups in Gapuk Village by utilizing cow dung so that its management can be processed optimally so that in the long term it is expected to be able to produce at affordable prices and environmentally friendly. This activity uses the following methods: a) counseling and face-to-face on the importance of processing cow dung into organic fertilizer, b) knowledge training on how to make organic fertilizer with cow dung and MA-11 decomposer, and c) demonstration of making organic fertilizer.